Usiłowanie zmiany ustroju państwa oraz usiłowanie usunięcia organów władzy jako zbrodnie stanu. Zarys problemu - Leniart, Ewa (My University, 2015)
This paper is a trial to analyze the shaping process of crimes of attempt to change the political system of the State and of attempt to change State authority agencies throughout centuries. These crimes, included among high treasons, have undergone evolution, both in respect of legal interpretation (subsumption of specific facts under the binding legal regulations) and judicial decisions, but also in respect to their meaning for power consolidation in the State. A specific expression of such an evolution was recognition of crimes of attempt to change the political system of the State and of attempt to change State authority agencies, regulated by Art. 86 of the criminal code of the Polish Army from 1944, following the Soviet law, as counterrevolutionary crimes. It was a new concept, alien to the Polish legal system, which in the period of communism enabled using regulations of criminal law to introduce and then to consolidate their power in Poland. Recognition as counterrevolutionary crime of an action whose origin were specific, political reasons that were unwelcome by the authorities, had a decisive influence upon qualification of human acts as unlawful acts that were high treasons. Quite independent of the political system, there are some legal regulations sanctioning responsibility for acts aimed at state authority agencies and the political system of the state. The science of law has elaborated in this respect some legal regulations that are uniform in all democratic countries. As it is shown by the history of criminal law, abuses in applications of regulations sanctioning criminal responsibility in connection with committing crimes of high treason may originate from misinterpretation of legal regulations and latitude in giving sentences in criminal proceedings, which took place on a large scale in Poland from 1944 to 1956.
CRIME OF ATTEMPT TO CHANGE THE POLITICAL SYSTEM